2022
DOI: 10.1093/toxsci/kfac011
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Secreted miRNA Biomarkers of Chemical-Induced Neurodegeneration in Human iPSC-Derived Neurons

Abstract: Elucidation of predictive fluidic biochemical markers to detect and monitor chemical-induced neurodegeneration has been a major challenge due to a lack of understanding of molecular mechanisms driving altered neuronal morphology and function, as well as poor sensitivity in methods to quantify low-level biomarkers in bodily fluids. Here, we evaluated five neurotoxicants (acetaminophen [negative control], bisindolylmaleimide-1, colchicine, doxorubicin, paclitaxel, and rotenone) in human iPSC-derived neurons to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…In Table , 16 out of the top 20 identified ncRNAs associated with DOX have been confirmed by referenced validations from the PubMed literature. For instance, a study evaluating neurotoxic chemicals in hiPSC-derived neurons observed the downregulation of miR-30d following exposure to DOX . Additionally, experiments demonstrating the overexpression of let-7b showcased enhanced apoptosis and reduced DOX resistance in chronic granulocytic leukemia cells …”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table , 16 out of the top 20 identified ncRNAs associated with DOX have been confirmed by referenced validations from the PubMed literature. For instance, a study evaluating neurotoxic chemicals in hiPSC-derived neurons observed the downregulation of miR-30d following exposure to DOX . Additionally, experiments demonstrating the overexpression of let-7b showcased enhanced apoptosis and reduced DOX resistance in chronic granulocytic leukemia cells …”
Section: Experiments and Resultsmentioning
confidence: 99%
“…For instance, a study evaluating neurotoxic chemicals in hiPSC-derived neurons observed the downregulation of miR-30d following exposure to DOX. 38 Additionally, experiments demonstrating the overexpression of let-7b showcased enhanced apoptosis and reduced DOX resistance in chronic granulocytic leukemia cells. 39 …”
Section: Experiments and Resultsmentioning
confidence: 99%